2022
DOI: 10.1111/apa.16316
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental disorders and somatic diagnoses in a national cohort of children born before 24 weeks of gestation

Abstract: Aim This study investigated childhood diagnoses in children born extremely preterm before 24 weeks of gestation. Methods Diagnoses of neurodevelopmental disorders and selected somatic diagnoses were retrospectively retrieved from national Swedish registries for children born before 24 weeks from 2007 to 2018. Their individual medical files were also examined. Results We studied 383 children born at a median of 23.3 (range 21.9–23.9) weeks, with a median birthweight of 565 (range 340–874) grams. Three‐quarters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 62 publications
4
34
0
Order By: Relevance
“…In this issue of Acta Paediatrica, Morsing and colleagues have interrogated two national databases to derive recorded diagnoses in childhood and have validated these conditions and procedures against medical records for babies born and surviving between 21 and 23 weeks of gestation up to 12 years of age. 2 It is heartening that most concur and that missing data are relatively few, which enhances the confidence in their conclusions and points to the importance of having well-designed and regularly used national systems utilising international disease classifications. Morsing and colleagues identify the pervasive number of problems experienced by survivors at follow-up with 75% having some neurodevelopmental problems and 88% a somatic diagnosis.…”
Section: E D I T O R I a L Meeting The Needs Of Our Smallest Survivorsmentioning
confidence: 99%
“…In this issue of Acta Paediatrica, Morsing and colleagues have interrogated two national databases to derive recorded diagnoses in childhood and have validated these conditions and procedures against medical records for babies born and surviving between 21 and 23 weeks of gestation up to 12 years of age. 2 It is heartening that most concur and that missing data are relatively few, which enhances the confidence in their conclusions and points to the importance of having well-designed and regularly used national systems utilising international disease classifications. Morsing and colleagues identify the pervasive number of problems experienced by survivors at follow-up with 75% having some neurodevelopmental problems and 88% a somatic diagnosis.…”
Section: E D I T O R I a L Meeting The Needs Of Our Smallest Survivorsmentioning
confidence: 99%
“…The vast majority (96%) of 383 Swedish children born at 22 or 23 weeks of gestation had at least one diagnosis when they were 2‐13 years of age. A national register‐based study by Morsing et al, 1 covering the period 2007‐2018, reported that 75% had neurodevelopmental disorders, such as attention‐deficit hyperactivity disorder or autistic spectrum disorder. In addition, 88% had selected somatic disorders, including asthma and cerebral palsy.…”
Section: The Prognosis For Micropreemies Is Not So Goodmentioning
confidence: 99%
“…At follow-up at ages 2-13 years, 4% of the 22-week GA children had died after discharge, 78% had neurodevelopmental and 87% somatic disorders -only one of 93 surviving children did not have a diagnosis. 3 The outcome was moderately better for infants born at 23 weeks, but they had a higher rate of severe cerebral morbidity as newborns than the survivors of GA 22 weeks.…”
mentioning
confidence: 93%
“…During these years, the rates of severe neonatal morbidities among the survivors did not change, except that necrotizing enterocolitis became more common for those born at GA 22 weeks. At follow‐up at ages 2–13 years, 4% of the 22‐week GA children had died after discharge, 78% had neurodevelopmental and 87% somatic disorders – only one of 93 surviving children did not have a diagnosis 3 . The outcome was moderately better for infants born at 23 weeks, but they had a higher rate of severe cerebral morbidity as newborns than the survivors of GA 22 weeks.…”
mentioning
confidence: 99%